109. Seroprevalence of Protective Antibodies against Varicella, Hepatitis-A and Dengue among Indian Children, Adolescents and Adults. (15th December 2022) - Verma, Sanjay; Baig, Mirza Zubair; Rawat, Ankita; Kapoor, Rajesh; Rawat, Amit; Suri, Vikas; Suri, Vanita
Abstract: Background: Varicella, Hepatitis-A and Dengue cause significant disease burden in our country. Estimation of age-wise seroprevalence of antibodies against these diseases not only help us in understanding age-specific incidence rates and susceptibility, but also help policy makers in deciding need and timing of vaccination. None of these vaccines are part of current national immunization program in India, yet. Methods: In this observational cross-sectional study, apparently healthy children (9-12 years), adolescents (15-18 years) and adults (25-30 years) attending OPD of a tertiary care hospital in Northern India over two-year period (July 17- June 19) were enrolled after taking informed written consent, and their 3-ml venous blood sample was collected. Ethical clearance was obtained from Institute Ethics committee, before enrolling subjects. Serum was tested for IgG antibodies using specific commercial ELISA kits. Those who received received Hepatitis-A or Varicella vaccination in past were excluded from enrollment. Results: Out of total 240 subjects (M:F=117:123) enrolled, 75 were children, 75 adolescents and 90 adults in specified age groups. Mean age in these three groups were 11.04, 16.52 and 26.53 years respectively. In our study, antibodies (IgG) against Varicella were > 12 U/ml (seroprotective) in 36% (27/75), 74.6% (56/75), 64.5% (58/90) in children, adolescent and adults in specified age groups, respectively. Similarly, the antibodies (IgG) against Hepatitis-A were > 10 U/ml (seroprotective) in above three groups were 68% (51/75), 85.3% (64/75), 95.5% (86/90). For dengue IgG antibodies also, seropositivity rates in above three groups were 37.3% (28/75), 62.7% (47/75), 53.3% (48/90). Conclusion: Large proportion of children, adolescents and adults remain susceptible to Varicella and Hepatitis-A infection in India. Early childhood vaccination with Varicella and Hepatitis-A vaccines should be a part of National Immunization Programme in India, as a part of preventive strategy. Our study also showed a large proportion of children, adolescents and adults remain seronegative for Dengue antibodies in various age groups. Therefore, if currently available dengue vaccine (Dengvaxia) has to be used in our population, it can only be used after individual screening. Disclosures: All Authors : No reported disclosures.